2006
DOI: 10.1002/eji.200535290
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐15 mediates protection against experimental tuberculosis: A role for NKG2D‐dependent effector mechanisms of CD8+ T cells

Abstract: CD8 + T cells are involved in protection againstMycobacterium tuberculosis infection and represent a promising target for new vaccine strategies. Because IL-15 is important for the homeostasis of CD8 + T cells, we studied the immune response in IL-15-deficient mice during tuberculosis. In the absence of IL-15, CD8 + T cells failed to efficiently accumulate in draining lymph nodes and at the site of infection. The expression of antigen-specific effector functions, such as the production of interferon-c and cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…The proliferation of antigen-specific CD8 ϩ T cells was not affected following anti-NKG2D treatment, because there were no differences in the total numbers of T cells or virusspecific CD8 ϩ T cells within the CNS following viral infection. Other reports indicate that blocking NKG2D on mouse CTLs negatively affects numerous effector functions, including proliferation, the production of IFN-␥, and lytic activity (41,60,64,74). There are several possible explanations for the results obtained from our experiments.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…The proliferation of antigen-specific CD8 ϩ T cells was not affected following anti-NKG2D treatment, because there were no differences in the total numbers of T cells or virusspecific CD8 ϩ T cells within the CNS following viral infection. Other reports indicate that blocking NKG2D on mouse CTLs negatively affects numerous effector functions, including proliferation, the production of IFN-␥, and lytic activity (41,60,64,74). There are several possible explanations for the results obtained from our experiments.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies have shown that blocking NKG2D receptor signaling diminishes IFN-␥ secretion by T cells (9,69,74). Given that IFN-␥ is important in the control of JHMV replication within the CNS and in host survival, it is plausible that anti-NKG2D treatment of JHMV-infected mice affects IFN-␥ secretion by infiltrating T cells (69).…”
Section: Nkg2d Receptor and Ligands Are Expressed In Response Tomentioning
confidence: 99%
See 2 more Smart Citations
“…IL-15 has been reported to participate in protection against M.tb infection [43]. This process could contribute to the high resistance to H37Ra even in the absence of iNOS.…”
Section: Adaptive Immune Responsementioning
confidence: 99%